Conflitos reais e soluções digitais: A transformação e a legitimidade do uso da tecnologia na resolução de disputa - Brito, Larissa Queiroz (2024)
Technology and artificial intelligence are increasingly present in everyday civil life, for example, in commercial dealings, education, entertainment, communication, work activities, etc. Their impact also affects the legal field through online dispute resolution, which makes it necessary to study this interaction so that it is something useful that adds to the ways of dealing with conflicts and does not represent a potential violation of rights. Therefore, the aim of this work is to analyze the level of contact between law and technology, specifically in dispute resolution, as a possible means of implementing the principle of access to justice, with the aim of analyzing the risks of using artificial intelligence, its mode of action and application in the legal scenario, as well as studying the condition of using online dispute resolution to propose legal action, the analysis of the practice of how technology can collaborate with the adequate solution of conflicts, both in the private sphere and in the Judiciary and the legitimacy of using artificial intelligence to make decisions. In order to deepen the research on the above, the analytical-descriptive research methodology was used, which seeks to verify the existing aspects between online dispute resolution and its adherence to the Brazilian legal system, by means of a case study and observation